THE INFLUENCE OF CHEMICAL COMPOSITION ON THE CORROSION RATE OF HIGH-CHROMIUM CAST IRON - V. V. Netrebko; I. P. Volchok (Литьë и металлургия)
The influence of the chemical composition on the corrosion rate of high-chromium cast iron was researched. During the castings’ cooling process the replacement of the atoms of nickel, iron and manganese by the atoms of chromium in the carbides took place. As a result, the areas with reduced chromium content were formed near carbides. After decreasing the chromium content in these areas below 12% the corrosion processes activated. Using the mathematical experimental design techniques the regression dependence between the corrosion rate of the cast irons and content of C, Cr, Mn and Ni in them was established. The conducted research showed that the minimum corrosion rate was observed in the cast iron containing: 1.09% C, 25.57% Cr, 0.6% Mn and 1.87% Ni. The obtained results allow predicting the corrosion rate of the high-chromium cast irons alloyed with Mn and Ni and may be used while establishing the new compositions of wear-resistant materials.